Influence of salinity on the development of the banana colonised by arbuscular mycorrhizal fungi - Almeida, Aldênia; Gomes, Vânia Felipe; Mendes Filho, Paulo; Lacerda, Claudivan; Freitas, Emanuel (Revista Ciência Agronômica, 2016)
This study evaluated the effect of salt stress on the growth of banana seedling colonized with mycorrhizal fungi (AMF) on a substrate from a Quartzipsamment. The experiment was conducted in a greenhouse, using a completely randomized design in split plots; the plots had 5 levels of salinity in irrigation water (0.5, 1.5, 2.5, 3.5 and 4 5 dS m-1) and the subplots of four collection periods (40, 60, 80 and 100 days after transplanting), with 4 repetitions, totaling 80 experimental units. The seedlings of banana cv. “Prata” was produced by micropropagation and inoculated with arbuscular mycorrhizal and acclimatization for 40 days. Evaluations were made of leaf gas exchange, shoot dry mass, nutrient content, mycorrhizal root colonization and spore density. Increased levels of salinity caused reduction in dry matter production and photosynthetic rate, which may be associated with osmotic effects of salts in the soil, the increase in sodium and reduced the levels of N in leaves. Salinity reduced root mycorrhizal colonization, but did not influence the density of AMF spores under the conditions of this study.